Assessing the Future of Renewable and Smart Grid Technologies in Regional Energy Systems - Frédéric Babonneau; Alain Haurie; Guillaume Jean Tarel; Julien Thénié (Swiss Journal of Economics and Statistics, 2012)
In this paper we present the regional techno-economic model ETEM, designed for the analysis of regional energy/environment systems and we show how it can be used to explore the possible penetration of new technologies in a region corresponding roughly to the canton of Geneva. We investigate three scenarios with different constraints on CO2 emissions and electricity imports and show the essential role played by new technologies, linked through a smart grid, in the effort toward a sustainable energy system. We strengthen our conclusion with a stochastic approach dealing with uncertainty in future electricity prices and electric car technology penetration.
Keywords: Q41; Q42; 330; smart-grids; renewable energy sources; Switzerland; Geneva